Pengaruh Konsentrasi Zat Pengatur Tumbuh Naphthalene Acetic Acid dan Benzil Amino Purin terhadap Pertumbuhan Protokorm Anggrek Dendrobium spectabile pada Kultur In Vitro - Ujang Siron; Noertjahyani Noertjahyani; Yana Taryana; Romiyadi Romiyadi (Paspalum: Jurnal Ilmiah Pertanian, 2019)
The aim of the article is to study the interaction effect between NAA and BAP concentration on protocorm growth and to know the proper concentration for growth of Dendrobium  spectabile  orchid protocorm. This research method using an experimental method which is conducted in the Laboratory of Agriculture Faculty of Winaya Mukti University, Tanjungsari Subdistrict, Sumedang District. The experiment was conducted from June 2017 until September 2017. The experiment used was a Completely Randomized Design (CRD) with the factorial pattern, consisting of two factors and repeated twice. the first factor was the effect of NAA concentration which consisted of five levels, namely without NAA, 0.5 mg kg-1, 1.0 mg kg-1, 1.5 mg kg-1, and 2.0 mg kg-1.  The second factor is the BAP concentration which consists of five levels, namel without BAP, 1.0 mg kg-1, 2.0 mg kg-1, 3.0 mg kg-1, and 4.0 mg kg-1. Eksplant is protocorm from orchid D. spectabile which is grown on MS medium (Murashig and Skoog) half recipe as base medium accompanied by each treatment for 12 weeks. The experimental results show that there is an interaction between the effect of NAA and BAP concentration on the number of leaves only. Without NAA or 1.5 mg kg-1 NAA concentration with BAP 2.0 mg kg-1 gives more leaves.  Independent of NAA or BAP concentrations did not affect the number of buds, number of roots, root length, fresh and dry weight of plantlets, and also growth ability of plantlets.  BAP concentration only affect plant height, and the highest plantlet height is found without add of BAP in medium culture